The Inhibition of Tissue Activator and Urokinase by Human Plasma - Walker, J E; Ogston, D (Thrombosis and Haemostasis, 1982)
Plasma reduced the activity of urokinase and, to a lesser extent, tissue activator on unheated fibrin plates. After depletion of plasminogen by lysine-Sepharose the inhibitory effect of plasma was increased.Normal plasma separated on DEAE-Sepharose or, after passage through lysine-Sepharose, on Sephadex G-100 provided fractions in three regions capable of inhibiting tissue activator. The high molecular weight fractions inhibited both activators, but after plasma fractionation on Sephadex 4B the inhibitory activities against tissue activator and urokinase eluted separately. Urokinase inhibition eluted with a2-macroglobulin: the inhibition of tissue activator was of higher molecular weight and of greater lability. Inhibition of tissue activator was found in two lower molecular weight regions: the fractions of one region inhibited tissue activator and coincided with the elution of fast-acting antiplasmin activity. The other region inhibited both tissue activator and urokinase. Alpha1 antitrypsin and antithrombin III eluted after both inhibitory regions.
Keywords: Urokinase; Tissue activator; Plasma inhibitors of fibrinolysis